2013
DOI: 10.1152/ajpregu.00195.2013
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of Per1 and Cry2 in the regulation of Per1 target gene expression in the liver and kidney

Abstract: Mounting evidence suggests that the circadian clock plays an integral role in the regulation of many physiological processes including blood pressure, renal function, and metabolism. The canonical molecular clock functions via activation of circadian target genes by Clock/Bmal1 and repression of Clock/Bmal1 activity by Per1–3 and Cry1/2. However, we have previously shown that Per1 activates genes important for renal sodium reabsorption, which contradicts the canonical role of Per1 as a repressor. Moreover, Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 62 publications
(106 reference statements)
4
39
0
Order By: Relevance
“…We (30) have also previously shown that Per1 and Cry2 modulate opposing actions on Per1 target gene expression in the kidney and liver and that Per1 heterozygous mice have an approximate 50% reduction in Per1 protein expression in these tissues. Therefore, to determine if Per1 regulates aldosterone levels, plasma aldosterone was assessed in WT and Per1 heterozygous mice by ELISA at noon (middle of the inactive phase) and midnight (middle of the active phase) under normal dietary conditions.…”
Section: Decreased Levels Of Per1 Are Associated With Lower Plasma Almentioning
confidence: 60%
See 4 more Smart Citations
“…We (30) have also previously shown that Per1 and Cry2 modulate opposing actions on Per1 target gene expression in the kidney and liver and that Per1 heterozygous mice have an approximate 50% reduction in Per1 protein expression in these tissues. Therefore, to determine if Per1 regulates aldosterone levels, plasma aldosterone was assessed in WT and Per1 heterozygous mice by ELISA at noon (middle of the inactive phase) and midnight (middle of the active phase) under normal dietary conditions.…”
Section: Decreased Levels Of Per1 Are Associated With Lower Plasma Almentioning
confidence: 60%
“…We (30) have recently shown that Per1 and Cry2 mediate opposing actions on Per1 target gene expression in the liver and kidney and that mice with reduced levels of Per1 have increased levels of Cry2. To test the effect of reduced Per1 on Cry2 adrenal gland cells and tissue, Cry2 mRNA levels were determined by quantitative PCR.…”
Section: Loss or Reduction Of Per1 Results In Increased Levels Of Crymentioning
confidence: 99%
See 3 more Smart Citations